HEPATOPROTECTIVE ACTIVITY OF ANOGEISSUS LATIFOLIA LEAF AND BARK EXTRACTS AGAINST CARBON TETRACHLORIDE INDUCED HEPATOTOXICITY IN RATS - K. M. M. PARVATHI, C. K. RAMESH, V. KRISHNA, K. SHANKARMURTHY, I. J. KUPPAST3; N. M. SHAKUNTALA4 (The Bioscan, 2013)
The study was designed to evaluate the hepatoprotective activity of Anogeissus latifolia leaf and bark extracts by using solvents viz. petroleum ether, chloroform and methanol. Hepatotoxicity was induced in Wistar rats by intraperitonial injection of CCl4 (0.1mL/kg/day for 10 days). The standard drug used was silymarin. Various extracts were given in the dose of 300mg/mL of all the extracts except chloroform leaf and methanolic bark which were prepared @ 200mg/mL, for 14 days. The hepatoprotective effect of these extracts was evaluated for liver function biochemical parameters (total bilirubin, serum protein, alanine aminotransaminase, aspartate aminotransaminase and alkaline phosphatase activities) and histopathological studies of liver. Treatment with methanolic leaf and bark extract significantly prevented the functional, physical, biochemical and histological changes induced by CCl4 indicating the recovery of hepatic cells. The results suggest that methanolic leaf and bark extract of Anogeissus latifolia possesses potential hepatoprotective activity.